Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Radiocarbon as a biomarker of urban pollution in leaves of evergreen species sampled in Rome and in rural areas (Lazio—Central Italy) - Alessio, M.; Anselmi, S.; Conforto, L.; Improta, S.; Manes, F.; Manfra, L. (Atmospheric Environment, 2002)
The aim of the present study is the use of 14 C, sampled in leaves of evergreen species, as a natural geochemical marker to estimate the contribution of artiﬁcial sources (heating plants, vehicles, etc.) to the complex of atmospheric gases in an urban environment. Leaves were chosen due to sampling easiness and their reliability: in particular the evergreen species, being exposed all the year round to pollutants are especially indicated for bioindication and biomonitoring studies. The response to atmospheric pollutants has been studied of two plant species (Quercus ilex L., Pinus pinea L.) measuring isotopic ( 14 r, d 13 C), chemical (Pb concentration) and ecophysiological (gaseous exchange and leaf ﬂuorescence of chlorophyll a) parameters. Leaves of holm-oaks and stone pine needles collected over a 3-year time span in an urban park in Rome (Villa Ada) and in reference localities outside the city on the Tyrrhenian coast and in the preAppennine area have been analysed. In Villa Ada measurements were carried out along a transect from the road bordering the park towards the interior; all the parameters, together in agreement, showed a decreasing pollution gradient towards the inner park. It was possible to estimate a 5.570.3% contribution of CO2 from fossil fuels close to the road, decreasing to 1.770.3% at o300 m from it towards the inner park. The isotopic analyses conducted on stone pines and holm-oaks show that 14 C provides indications on the degree of pollution from fossil fuels, while d 13 C appears to be conditioned mainly by the interspeciﬁc difference, and also by many other environmental factors that affect the plant functionality. Results conﬁrmed that radiocarbon is a useful tool in environmental studies, allowing to quantify the contributions of CO2 of anthropic origin: this parameter, together with appropriate isotopic, chemicaland ecophysiological analyses, could provide a good indication of the ‘‘air quality’’ in urban and rural contexts.
Keywords: air quality; carbon isotopes; co 2; lead; photosynthesis

Radiocarbon as a biomarker of urban pollution in leaves of evergreen species sampled in Rome and in rural areas (Lazio—Central Italy) - Alessio, M; Anselmi, S; Conforto, L; Improta, S; Manes, F; Manfra, L (Atmospheric Environment, 2002)
The aim of the present study is the use of 14 C, sampled in leaves of evergreen species, as a natural geochemical marker to estimate the contribution of artiﬁcial sources (heating plants, vehicles, etc.) to the complex of atmospheric gases in an urban environment. Leaves were chosen due to sampling easiness and their reliability: in particular the evergreen species, being exposed all the year round to pollutants are especially indicated for bioindication and biomonitoring studies. The response to atmospheric pollutants has been studied of two plant species (Quercus ilex L., Pinus pinea L.) measuring isotopic ( 14 r, d 13 C), chemical (Pb concentration) and ecophysiological (gaseous exchange and leaf ﬂuorescence of chlorophyll a) parameters. Leaves of holm-oaks and stone pine needles collected over a 3-year time span in an urban park in Rome (Villa Ada) and in reference localities outside the city on the Tyrrhenian coast and in the preAppennine area have been analysed. In Villa Ada measurements were carried out along a transect from the road bordering the park towards the interior; all the parameters, together in agreement, showed a decreasing pollution gradient towards the inner park. It was possible to estimate a 5.570.3% contribution of CO2 from fossil fuels close to the road, decreasing to 1.770.3% at o300 m from it towards the inner park. The isotopic analyses conducted on stone pines and holm-oaks show that 14 C provides indications on the degree of pollution from fossil fuels, while d 13 C appears to be conditioned mainly by the interspeciﬁc difference, and also by many other environmental factors that affect the plant functionality. Results conﬁrmed that radiocarbon is a useful tool in environmental studies, allowing to quantify the contributions of CO2 of anthropic origin: this parameter, together with appropriate isotopic, chemicaland ecophysiological analyses, could provide a good indication of the ‘‘air quality’’ in urban and rural contexts.
Keywords: air quality; carbon isotopes; co 2; lead; photosynthesis

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). - Prasad, M N; Freitas, H (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.
Keywords: Biosorption; cadmium; chromium; copper; desorption; lead; Nickel; phytomass; Quercus ilex; root; stem

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). - Prasad, M. N.; Freitas, H. (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.
The following values have no corresponding Zotero field: accession-num: 15092842
Keywords: Biosorption; cadmium; chromium; copper; desorption; lead; Nickel; phytomass; Quercus ilex; root; stem

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution